Postural orthostatic tachycardia syndrome: pathophysiology, management, and experimental therapies. (3rd October 2022) - Narasimhan, Bharat; Aggarwal, Devika; Satish, Priyanka; Kantharia, Bharat; Aronow, Wilbert S.
ABSTRACT: Introduction: Postural orthostatic tachycardia syndrome (POTS) is an increasingly well-recognized condition encountered in clinical practice. Diagnosis and treatment remain extremely challenging. The limited success of currently available therapies has laid the foundation for a number of experimental therapies. Areas Covered: In this review, we will briefly outline the pathophysiology and clinical features of this syndrome, before moving on to its management, with a specific focus on experimental pharmacological therapies. Finally, we briefly discuss POTS related to the SARS CoV-2 (COVID-19) pandemic. Expert Opinion: Despite tremendous advances, the diagnosis and management of POTS remains extremely challenging. The multitude of contributory mechanisms, which predominate to varying degrees in different patients further complicates management. Improved characterization of pathophysiological phenotypes is essential to individualize management. Lifestyle measures form the first line of therapy, followed by beta-blockers, ivabradine, fludrocortisone, and midodrine. Supplemental therapies such as iron, vitamin D and α lipoic acid are quite safe and a trial of their use is reasonable. The use of erythropoietin, IVIG, desmopressin, etc., are more specialized and nuanced alternatives. In recent years, interest has grown in the use of cardiac neuromodulation. Though preliminary, some of these therapies are quite promising.